Direct dentin bleaching: Would it be possible? - Clemente, Camila Ferro [UNESP]; de Alcântara, Sibele [UNESP]; da Silva, Lívia Maria Alves Valentim [UNESP]; Esteves, Lara Maria Bueno [UNESP]; Catelan, Anderson [UNESP]; Aidar, Karen Milaré Seiscento [UNESP]; Fagundes, Ticiane Cestari [UNESP]; Briso, André Luiz Fraga [UNESP] (Elsevier, 2022)
This study aims to evaluate in vitro the effect of violet LED when applied directly to dentin tissue pigmented by different substances. We analyzed the chromatic alteration, the bleaching effect and the temperature variation. Hence, 60 bovine dentin tissue discs were divided into five groups: N[sbnd]Natural Pigmentation; T-Black Tea; C-Soluble Coffee; W-Red Wine; B-Equine Blood. Individualized pigmentation protocols were performed and all groups reached the same chromatic change value. Subsequently, we simultaneously performed a bleaching session and measured temperature variation using a K-type thermocouple device. Data on chromatic change (∆E, ∆E00, ∆a, ∆b and ∆L), whitening effect (WID) and temperature variation were subjected to one-way Anova and Tukey's post-test at a 5% significance level. The C group showed the most relevant chromatic change values, similar to the N group, responding positively to the treatment. However, the B group differed from the control group, which showed difficulty to respond to the treatment. Regarding the whitening index, only the W group showed lower results than the others. The B group showed the greatest temperature changes. We conclude that the violet LED offered chromatic change, which generated a bleaching effect. Pigmentations with red wine and blood showed the greatest difficulty to respond to treatment, also promoting a higher temperature rise in teeth pigmented with blood.
Keywords: Dental bleaching; Dentin; Pigmentation; Violet LED